Migration and spatial misallocation in China - LI, Xiaolu (Institutional Knowledge at Singapore Management University, 2023)
We structurally estimate the ﬁrm-level frictions across prefectures in China and quantify their aggregate and distributional implications. Based on a general equi-librium model with input and output distortions and migration, we show that the ﬁrm-level frictions are less dispersed and less correlated with productivity in richer prefectures. Counterfactual exercises show that reducing the within-prefecture mis-allocation increases the aggregate welfare, discourages migration towards large cities, and narrows the spatial inequality. Moreover, internal migration alleviates the impacts of micro-frictions on aggregate welfare and worsens their impacts on spatial inequality.